Prognostic Factors and Outcome of Patients with Adult Acute Lymphoblastic Leukemia Treated with the Hyper-CVAD Regimen: A Retrospective Study - Zahra Malakoutikhah; Farzaneh Ashrafi; Ali Derakhshandeh (Advances in Hematology)
Aim. The Hyper-CVAD regimen has shown promising results for adult patients with acute lymphoblastic leukemia (ALL), as designed by the MD Anderson Cancer Center (MDACC). This treatment has resulted in a complete remission rate of 92% and a 5-year overall survival of 38%. However, given the diversity of patient demographics and institutional methods, outcomes may differ between various institutions. This study will compare the outcome of adult ALL patients treated with the Hyper-CVAD regimen in Iran with those obtained in the original series presented at the MDACC. Patients and Method. In this retrospective study, we evaluated the 2-year leukemia-free survival (LFS) and the 2-year overall survival (OS) of 70 ALL patients treated between 2014 and 2019 in the Seyed Al-Shohada Hospital in Isfahan, Iran. Results. In total, 59 ALL patients (84.28%) achieved complete remission (CR). The CR rate had statistical differences by bone marrow transplantation (BMT) and WBC count. The 2-year LFS and OS were 40% and 42%, respectively. There were significant differences in LFS and OS by BMT, myeloid marker, and WBC count. Conclusion. The outcome of the traditional Hyper-CVAD regimen in treating adult ALL was not satisfying. More efficient therapies should be applied for the treatment of adult ALL.